2008
DOI: 10.2486/indhealth.46.112
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Low Back Pain and Occupational Risk Factors among Taxi Drivers

Abstract: A survey of taxi drivers was conducted to determine the actual situation of drivers' low back pain (LBP). The survey was carried out in October 2002, the target drivers were asked to complete a questionnaire which contains questions regarding physique of drivers, demographic features, working conditions, office environment, health conditions, the presence of low back pain, the level of low back pain based on Visual Analogue Scale and Roland-Morris Disability Questionnaire score. As a result, the total number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
39
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 15 publications
(19 reference statements)
11
39
1
5
Order By: Relevance
“…The mean values of the height, HC, BMI and WHR were similar to the study by Andrews R et al 12 These values were higher than the values in the studies by Naidoo M and Miyamoto M, et al et al and may be explained by the fact that Africans as represented in this study and the study by Andrews R et al are bigger in stature than Asians as reported in the studies by Naidoo M and Miyamoto M, et al [12][13][14] The LSA in this study had a wide range and this may explain the difference in mean angles from various studies. 6,8,13,15,16 The mean LSA of our subjects was significantly higher than the mean value of 31.7 0 reported by Kim HS et al and 32.4 0 reported by Chung HJ et al 15,16 It was however significantly lower than the mean values in the studies by Fernard R et al (46.5 0 ) and Middleditch A et al (42.5 0 ).…”
Section: Discussionsupporting
confidence: 84%
“…The mean values of the height, HC, BMI and WHR were similar to the study by Andrews R et al 12 These values were higher than the values in the studies by Naidoo M and Miyamoto M, et al et al and may be explained by the fact that Africans as represented in this study and the study by Andrews R et al are bigger in stature than Asians as reported in the studies by Naidoo M and Miyamoto M, et al [12][13][14] The LSA in this study had a wide range and this may explain the difference in mean angles from various studies. 6,8,13,15,16 The mean LSA of our subjects was significantly higher than the mean value of 31.7 0 reported by Kim HS et al and 32.4 0 reported by Chung HJ et al 15,16 It was however significantly lower than the mean values in the studies by Fernard R et al (46.5 0 ) and Middleditch A et al (42.5 0 ).…”
Section: Discussionsupporting
confidence: 84%
“…4 Assaults and violent acts resulting in lost work days are higher as well (3.7 assaults per 10,000 in taxi drivers compared to 2.4 per 10,000 workers in other occupations). 3 Musculoskeletal disorders are common 3,6,7,12,14 (68.4 musculoskeletal disorders per 100,000 drivers compared to 35.4 per 100,000 workers in other occupations). 3 Overall poor working conditions include long hours, high stress, and poor health status 2 as well as lack of health and workers' compensation insurance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand however, other research has suggested that LBP is not related to hormonal fluctuations during the menstrual cycle nor to the use of Oral Contraceptives (OC) 14) . Back pain is known to be an increasingly common problem for the Japanese workforce 15) and has been studied epidemiologically in a variety of occupational fields such as construction workers 16) , taxi drivers 17) and school personnel [18][19][20] . The Japanese health care workforce is also known to suffer LBP, with previous research revealing high rates of musculoskeletal disorders among hospital nurses 6,8,21) and nursing home workers [22][23][24] .…”
mentioning
confidence: 99%